Subcutaneous filariasis: An unusual case report - Valand Arvindbhai; Pandya Bhanumati; Patil Yoganand; Patel Lalita (Wolters Kluwer Medknow Publications, 2007)
Wuchereria bancrofti presented in subcutaneous nodule is a very rare presentation. Wuchereria bancrofti first reported by Bancrofti in Brisbane in 1876 and the name filaria Bancrofti was given in 1877 and the generic name was given in 1878. A 15-year-old male patient′s known case of pulmonary Koch′s with incidentally detected subcutaneous nodule on right arm pit, cytology from the nodule shows many sheathed microfilaria along with segment of an adult female worm. Wet mount peripheral blood smear shows nocturnal motile microfilaria. The Wuchereria bancrofti is known to be associated with pulmonary Koch′s. Nocturnal motility and cytomorphological features differentiate Wuchereria bancrofti from Wuchereria loa loa . After giving diethyl carbamazine (DEC 6 mg/kg) for 21 days without disturbing anti Koch′s treatment schedule and microfilaria disappeared from peripheral blood.